Bacterial Spore mRNA – What’s Up With That? - Setlow, Peter; Christie, Graham (Frontiers in Microbiology, 2020)
Bacteria belonging to the orders Bacillales and Clostridiales form spores in response to nutrient starvation. From a simplified morphological perspective, the spore can be considered as comprising a central protoplast or core, that is enveloped sequentially by an inner membrane, a peptidoglycan cortex, an outer membrane and a proteinaceous coat. All of these structures are characterised by unique morphological and/or structural features, which collectively confer metabolic dormancy and properties of environmental resistance to the quiescent spore. These properties are maintained until the spore is stimulated to germinate, outgrow and form a new vegetative cell. Spore germination comprises a series of partially overlapping biochemical and physicochemical events – efflux of ions from the core, rehydration and inner membrane reorganization, disassembly of cortex and coat – all of which appear to take place in the absence of de novo ATP and protein synthesis. If the latter points are definitive, which they almost certainly are, why then do spores of all species examined to date contain a diverse range of mRNA molecules deposited within the spore core? Are some of these molecules ‘functional’, serving as translationally active units that are required for efficient spore germination and outgrowth, or are they just remnants from sporulation whose sole purpose is to provide a reservoir of ribonucleotides for the newly outgrowing cell? What is the fate of these molecules during spore senescence, and indeed, are conditions within the spore core likely to provide any opportunity for changes in the transcriptional profile of the spore during dormancy? This review encompasses a historical perspective of spore ribonucleotide biology, from the earliest biochemical led analyses – some of which in hindsight have proved to be remarkably prescient – through the transcriptomic era at the turn of this century, to the latest Next Generation sequencing derived insights. We provide an overview of the key literature to facilitate reasoned responses to the aforementioned questions, and many others, prior to concluding by identifying the major outstanding issues in this crucial area of spore biology.